Ocular Manifestations and Clinical Implications of Serum Immunoglobulin G4 Levels in Graves' Ophthalmopathy Patients. (3rd April 2022) - Luo, Ban; Yuan, Xu; Wang, Wei; Zhang, Jing; Liu, Rong; Hu, Weikun; Qi, Xin; Xiang, Nan; Chen, Liwen
ABSTRACT: Purpose: To investigate the association between serum immunoglobulin G4 (IgG4) levels and laboratorial parameters. Moreover, the ocular manifestations were compared in Graves' ophthalmopathy (GO) patients. Methods: Fifty-seven GO patients and fifty sex- and age-matched euthyroid subjects were enrolled. Serum IgG4 and immunoglobulin G (IgG) levels, thyroid hormones and thyroid autoantibodies were measured in all participants. Ophthalmologic examinations were performed to GO patients. Results: Serum IgG4 levels were increased in GO patients compared with euthyroid subjects (p<0.001). Multivariate analysis showed that TRAb levels were correlated with IgG4 levels in GO patients (β=1.45, p = 0.024). There were eight GO patients with IgG4 levels ≥ 135 mg/dL. They all had both eyelids swelling and the differences of HER were less than 2mm. Seven patients (7/8) showed bilateral symmetrical thickening of the extraocular muscles. Conclusions: Bilateral symmetry of ocular manifestation was observed in GO patients with IgG4 levels ≥135 mg/dL. IgG4 levels may be helpful in monitoring GO and diagnosing a new subtype of GO.